Screening Auschwitz Wanda Jakubowska's The Last Stage and the Politics of Commemoration - Haltof, Marek (Cultural Expressions, 2018)
This book about the early screen representation of Auschwitz-Birkenau deals with the classic Holocaust film made in 1948 in Poland by Auschwitz survivor, director Wanda Jakubowska. The Last Stage (or The Last Stop) is a pioneering work - the first narrative film to portray the former Nazi German camp. Haltof discusses Jakubowska's life and career before World War II, her imprisonment during the war, the prominent role that she played in the nationalized postwar Polish cinema, and problems she faced during the script stage. The monograph also discusses the unusual circumstances that surrounded the production of the film at Auschwitz-Birkenau and summarizes critical debates surrounding its release. Screening Auschwitz is the first detailed monograph on this classic Holocaust film. The book incorporates new materials and sources obtained through extensive archival research, and examines the impact of the film on other Holocaust narratives.